Enforcing CSR among food manufacturers in Malaysia through legal and institutional framework - Mark Louis,; Angelina Anne Fernandez,; Muhammad Afiq Ahmad Tajuddin,; Rahmah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Corporate Social Responsibility (CSR) is a concept in which corporations take into account the interest of the society in four areas of responsibility namely economic, legal, ethical, and philanthropic. In the area of food manufacturing, corporate social responsibility plays a vital role by ensuring that food is healthy and in adherence to safety standards. The Food Act 1983 and Food Regulations 1985 play an important role in enforcing corporate social responsibility amongst food manufacturers. Institutional framework in Malaysia such as, Ministry of Health, Food and Safety Quality Division and FOSIM were established to ensure that food-processing activities are according to the required hygiene and safety standards.It is discovered through National Consumer Complaint Centre reports that the enforcement in food safety needs improvement. The paper also examines the role of non-governmental agencies, namely, the Consumer Association of Penang and the National Consumer Complaints Centre, in channeling and documenting complaints from consumers to relevant enforcement agencies. This paper intends to analyse the duties of food manufacturers and to identify legislations that enforce CSR amongst food manufacturers. Adopting the content analysis method, this paper will examine the principle of CSR as contained in the Food Act 1983. This paper further discusses the roles of institutional frameworks namely, the Ministry of Health, Food Safety and Quality Division and FOSIM in enforcing corporate social responsibility amongst food manufacturers.This article aims to contribute namely to various stakeholders ie: the government in which CSR policies can be connected to food safety through our hard and soft laws and consumers will be more aware and educated in which they will support food companies that are implementing CSR in their food production. The paper also serves as a guide to food manufacturers as they will be more particular in their CSR efforts to garner more support towards their food products. With a good CSR policy and food safety efforts Malaysia will be able to increase its revenue in import and export of food products.